Group‐based shame, guilt, and regret across cultures. (20th February 2022) - de Groot, Marlies; Schaafsma, Juliette; Castelain, Thomas; Malinowska, Katarzyna; Mann, Liesbeth; Ohtsubo, Yohsuke; Wulandari, Maria Theresia Asti; Bataineh, Ruba Fahmi; Fry, Douglas P.; Goudbeek, Martijn; Suryani, Angela
Abstract: To date, there has been no systematic examination of cross‐cultural differences in group‐based shame, guilt, and regret following wrongdoing. Using a community sample ( N = 1358), we examined people's reported experiences of shame, guilt, and regret following transgressions by themselves and by different identity groups (i.e., family, community, country) in Burkina Faso, Costa Rica, Indonesia, Japan, Jordan, the Netherlands, Poland, and the United States. We assessed whether any variation in this regard can be explained by the relative endorsement of individualistic or collectivistic values at the individual level and at the country level. Our findings suggest that people's reported experience of these emotions mostly depends on the transgression level. We also observe some variation across individuals and countries, which can be partially explained by the endorsement of collectivistic and individualistic values. The results highlight the importance of taking into account individual and cultural values when studying group‐based emotions, as well as the identity groups involved in the transgression.